ANTIBACTERIAL ACTIVITY OF MANGOSTEEN BARK FRACTION (GARCINIA MANGOSTANA L.) SALMONELLA TYPHI ATCC 13311 - Anggraini, Salmah Wilujeng; Erikania, Susanti; Maritha, Vevi (Faculty of Vocational Studies, Universitas Airlangga, 2022)
Background: Typhoid fever is caused by Salmonella typhi bacterial infection which spreads via the faecal-oral route and has epidemic potential. Salmonella typhi is a Gram-negative bacterium in the Enterobacteriaceae family. Currently, the use of natural ingredients can be an alternative treatment for typhoid fever, one of which is the mangosteen stem skin (Garcinia mangostana L.). Purpose: To determine the antibacterial activity of mangosteen stem skin fraction against Salmonella typhi ATCC 13311. Method:The maceration method was selected using methanol solvent and fractionation by ECC using ethyl acetate and n-hexane as solvents. This study used five treatments (fraction with a concentration of 20%, 40%, 80%, chloramphenicol 30µg as a positive control, and DMSO as a negative control) which tested their antibacterial activity against Salmonella typhi ATCC 13311 by disc diffusion. Result: The results showed that the ethyl acetate fraction of mangosteen stem skin had the greatest average inhibition zone, that is 13.86 ± 0.72 mm compared to the n-hexane fraction of mangosteen stem skin with an inhibition zone of 10.43 ± 0.73 mm. The data obtained were then analyzed with One-way ANOVA. Conclusion: The results obtained were p=0.000 (sig <0.05), indicating that there was a significant difference between the ethyl acetate fraction and the n-hexane fraction with 20%, 60%, and 80% concentrations with positive control